The Use of Graphic Organizer Strategies to Improve Students' Writing Skills in English Language Teaching - Muhammad Labib Al Halim (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2024)
This research is motivated by the weak ability of students' writing in learning English. This research was conducted with the aim of improving English language skills, especially writing skills through the use of the graphic organizer strategy. This research was conducted on first semester students at Billfath Lamongan University. The subjects of this research were students of the English program from several research programs totaling 34 students. This research uses a Classroom Action Research design by Kemmis and Mc Taggart model in four stages, namely planning, implementing action, observing, and reflecting. The results of the preliminary test showed that students' writing skills were still low. The results of the assessment on the practice of writing texts using the assessment rubric show that there are still many students who have not reached the mark according to the criteria. The percentage of scores obtained by students are dominated by the